OPTIMIZING ROAD INFRASTRUCTURE MANAGEMENT IN BULGARIA VIA DIGITAL TOOLS AND ISO 55000 UNDER UNCERTAINTY - Steliyanov, Metodiy (E-Journal VFU, 2025)
Road infrastructure is a strategic national resource that is of key importance for economic development, territorial connectivity and social mobility in Bulgaria. However, asset depreciation, chronic financial insecurity and lack of maintenance pose serious challenges to its sustainable management. Traditional reactive management approaches have proven ineffective, which is why this article proposes a conceptual framework for transforming the management approach to road assets in Bulgaria. The model requires an integrated application of digital technologies and the management principles of ISO 55000.